Characterization of the Interaction Between SARS-CoV-2 Membrane Protein (M) and Proliferating Cell Nuclear Antigen (PCNA) as a Potential Therapeutic Target - Zambalde, Érika Pereira; Pavan, Isadora Carolina Betim; Mancini, Mariana Camargo Silva; Severino, Matheus Brandemarte; Scudero, Orlando Bonito; Morelli, Ana Paula; Amorim, Mariene Ribeiro; Bispo-dos-Santos, Karina; Góis, Mariana Marcela; Toledo-Teixeira, Daniel A.; Parise, Pierina Lorencini; Mauad, Thais; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
SARS-CoV-2 is an emerging virus from the Coronaviridae family and is responsible for the ongoing COVID-19 pandemic. In this work, we explored the previously reported SARS-CoV-2 structural membrane protein (M) interaction with human Proliferating Cell Nuclear Antigen (PCNA). The M protein is responsible for maintaining virion shape, and PCNA is a marker of DNA damage which is essential for DNA replication and repair. We validated the M-PCNA interaction through immunoprecipitation, immunofluorescence co-localization, and PLA (Proximity Ligation Assay). In cells infected with SARS-CoV-2 or transfected with M protein, using immunofluorescence and cell fractioning, we documented a reallocation of PCNA from the nucleus to the cytoplasm and the increase of PCNA and γH2AX (another DNA damage marker) expression. We also observed an increase in PCNA and γH2AX expression in the lung of a COVID-19 patient by immunohistochemistry. In addition, the inhibition of PCNA translocation by PCNA I1 and Verdinexor led to a reduction of plaque formation in an in vitro assay. We, therefore, propose that the transport of PCNA to the cytoplasm and its association with M could be a virus strategy to manipulate cell functions and may be considered a target for COVID-19 therapy.